Asas-asas Reformasi Pemikiran dalam Islam - Bustamam-Ahmad, Kamaruzzaman (Jurnal Usuluddin, 2006)
This article attempts to describe the basics reformation (islÄh) according to Islamic teaching. Therefore, this study will deal with a research on the concept of reformation in Islam either in theoritical concept or Islamic movement. The main point of this research is to provide a view that reformations which had occured in Muslims states cannot put aside the implementation of administration aspects according to Islam.